Social Restrictions in the COVID-19 Pandemic As a Traumatic Experience: Psycholinguistic Markers - Kostruba, Natalia (East European Journal of Psycholinguistics, 2021)
The COVID-19 pandemic has affected all aspects of life including psychological well-being. Social restrictions, changes in habits, and permanent stay at home might have a negative impact on the psychological state of people. The purpose of our study is to conduct a psycholinguistic analysis of pandemic narratives to identify markers of traumatic experience and identify possible gender differences. The sample consisted of 167 respondents (72% females). The mean age of participants was 21.09 years (SD = 4.52). The study was conducted in Ukraine online in 2020, during the second wave of lockdown. The audience was asked to write a narrative on “How my life changed during the COVID-19 pandemic. Personal experience”. As a result, we have found psycholinguistic markers that confirm the traumatic experience. Among them were the markers of time, depersonalization, and affective processes. A clear distinction of experience before and after the pandemic was detected in the narratives. This is characteristic of traumatic experience. In samples, such a distinction is made using the words “was” and “became”. The psychological marker of affective processes indicates immersion in a traumatic event. This discomposure is reflected in the manifestation of negative emotions through the words “bad”, “problems”, “critical”, and “difficult”. The main semantic markers in pandemic narratives are time and life. The life marker was meaningfully represented by stories about social limitations and physical health. Distinctions in pandemic descriptions of men and women have been revealed as psycholinguistic and semantic markers are different. Narratives of women are larger, they use more words (pronouns, adverbs and conjunctions, interrogatives and quantifiers) than men. Regarding content, men are more likely to talk about affective processes, while women − about social and biological ones. Our study is a maiden attempt to reflect on the pandemic as a traumatic event within the collective experience.